Anjing dan Intrik Haji Mutamakkin dalam Serat Cebolek (Perlawanan Ulama pada Rezim dalam Hermeneutika Refleksi Paul Ricoeur) - Abdul Rosyid (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2022)
Abstract: Haji Mutamakkin was a Javanese cleric in the era of the reigns of Amangkurat IV and Pakubuwono II. Ketib Anom (a palace cleric) ruled that he had violated the Islamic faith by owning a dog named Abdul Kahar and Kamarludin. These two names sounded similar to a Khatib and a Mataram Palace official. This study aimed to discover Haji Mutamakkin's motivations for owning a dog. As a cleric, of course, this was a controversial action and violated the Shari'a. Haji Mutamakkin was described as a controversial figure in Serat Cebolek, in contrast to the opinion of the people around Kajen, who considered him as Allah's guardian. The focus of this is, what was Haji Mutamakkin's motive for naming his two pet dogs? So far, when people talk about Haji Mutamakkin, they only see his Sufistic thoughts, even though there are many sides that have not been revealed, one of which is what we reveal in this research. This study applied a literature with a qualitative descriptive method. This research approach is the study of cultural communication and phenomenological hermeneutics of Paul Ricoeur. This study found that the political transition from Amangkurat IV to Pakubuwono II benefited Haji Mutamakkin. It was proven by granting an amnesty from Pakubuwono II to Haji Mutamakkin, so he was not sentenced to death.The Keraton cleric’s accusations about Haji Mutamakkin's pet dogs did not bother Pakubuwono II; in fact, he believed that Haji Mutamakkin's actions were part of cultural communication and political resistance to Palace officials who only served personal interests, as Patih Danuraja did when he conspired with VOC.